2019
DOI: 10.3389/fpsyg.2019.01444
|View full text |Cite
|
Sign up to set email alerts
|

It’s Been a Hard Day’s Night and I’ve Been Working Like a Dog: Workaholism and Work Engagement in the JD-R Model

Abstract: The study investigates if the job-demands resources (JD-R) model could be improved by including workaholism in its health impairment process. Salient predictors and antecedents of workaholism and work engagement are identified in a sample of 12170 employees at Norwegian universities and university colleges. Structural equation modeling suggested that job demands and job resources relate to workaholism and work engagement, respectively. The results also revealed that both workaholics and work-engaged employees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 85 publications
0
15
0
1
Order By: Relevance
“…In this case, as the representative core of organizations, CEOs are recommended to show more dedication to and absorption in their work and to demonstrate positive working attitudes among their TMT members, thus encouraging TMT members to strive for success and make more contributions to organizations. However, previous studies have also demonstrated the potential negative effects of workaholism on individuals themselves and their families (i.e., Langseth-Eide, 2019 ). Therefore, it should also be noted that workaholism tendency may have harmful influence for CEOs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, as the representative core of organizations, CEOs are recommended to show more dedication to and absorption in their work and to demonstrate positive working attitudes among their TMT members, thus encouraging TMT members to strive for success and make more contributions to organizations. However, previous studies have also demonstrated the potential negative effects of workaholism on individuals themselves and their families (i.e., Langseth-Eide, 2019 ). Therefore, it should also be noted that workaholism tendency may have harmful influence for CEOs.…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, we also respond to the call for more examinations about the specific mechanisms through which leader workaholism impacts subordinates (Li and She, 2020 ). In addition, prior research has focused almost exclusively on the negative effects of workaholism (i.e., Robinson et al, 2001 ; Schaufeli et al, 2008 ; Dordoni et al, 2019 ; Langseth-Eide, 2019 ), despite Ng et al's ( 2007 ) claims stressing the potential positive effects of workaholism. Hence, we extend past research by suggesting that workaholic CEOs can motivate their TMT members and thus promote firm performance to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This happens through two distinct psychological processes: either the health-impairment process or the motivational process [ 2 ]. The health impairment process posits that job demands lead to burnout [ 4 ] or workaholism [ 5 , 6 ], which in turn leads to ill health. On the other hand, the motivational process posits that job resources first lead to work engagement and thereafter to positive organizational outcomes [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Airila et al [ 3 ] revealed that engagement mediated the relationship between job and personal resources and work ability, in which the latter includes being healthy enough to perform the job. Moreover, Langseth-Eide [ 5 ] revealed that workaholism was negatively related to work-related health but that work engagement was positively related to work-related health, although both workaholics and engaged employees worked overtime hours. Additionally, previous studies have revealed that engaged employees report fewer psychosomatic complaints [ 30 ]; suffer less from head pain, cardiovascular problems and abdominal pain [ 9 ]; and report better self-reported health [ 31 ].…”
Section: Introductionmentioning
confidence: 99%